The Morphology, Feeding Habit and Toxicity Studies of Carinotetraodon borneensis and Carinotetraodon salivator - Ling, Jessie Fung Fung (Universiti Malaysia Sarawak (UNIMAS), 2009)
Identification of morphology, feeding habit and analysis of toxicity were carried out on two species of freshwater puffer fish, Carinotetraodon borneensis and Carinotetraodon salivator from Balai Ringin, Kuching. Samples of 120 fish with total lengths ranging from 5.0 cm to 6.5 cm were collected by gill nets and trap nets between August 2008 and December 2008. The physical appearances such as spines zone, nostril and teeth were observed by naked eyes and the numbers of dorsal, caudal and anal fin rays were counted using dissecting microscope. From the results, the standard length and body weight ranged from 4.0 cm to 5.3 cm and 6.2 g to 13.8 g respectively and shows significant difference in size between male and female. C. borneensis and C. salivator are omnivores which prey on benthic invertebrates as their food. The food preferences for both puffer fishes are zooplankton, nematodes, copepod, prawns, gastropods and polychaete. The toxicity level was tested by using mouse bioassays. Toxin was extracted from tissues of muscle, skin, and liver and injected to white mouse. The responses of the mouse were recorded and the mouse unit relation for tetrodotoxin was counted. The results show that the toxin is highly concentrated in livers of C. salivator, with scores ranging from 2.74 MU/g to 3.94 MU/g. The toxin of muscle and skin of both puffers were not detected. The fish has low toxicity and are considered non toxic.